2010
DOI: 10.1007/s12010-010-9051-8
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Naphthol Blue Black using the Horseradish Peroxidase

Abstract: This study evaluates the potential of the enzyme horseradish peroxidase in the decolorization of one common industrial azo dye, naphthol blue black. Studies are carried out to understand the process parameters such as pH, temperature and reaction time. The enzymatic decolorization of the dye was examined by UV-Vis spectrophotometer and LC-MS measurements. Temperature and pH conditions were optimized for obtaining high azo-dye decolorization. Azo-dye removal at a pH range 4-6 was found to be the highest for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…No color change was observed in all control flasks containing the dye in aqueous solutions at different pH without enzyme. It has been reported that HRP showed the best activity at pH 5 [17,28,29]. The results of this study are in agreement with the ones obtained by Dong et al [29], suggesting that decolorization might be due to the HRP activity.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…No color change was observed in all control flasks containing the dye in aqueous solutions at different pH without enzyme. It has been reported that HRP showed the best activity at pH 5 [17,28,29]. The results of this study are in agreement with the ones obtained by Dong et al [29], suggesting that decolorization might be due to the HRP activity.…”
Section: Resultssupporting
confidence: 92%
“…At the two extreme pH values (i.e. pH 3.0 and 8.0), decolorization was not observed because of the activity of HRP was lost at this pHs [17]. No color change was observed in all control flasks containing the dye in aqueous solutions at different pH without enzyme.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In accordance with our findings, direct yellow 4 was excellently decolorized at pH 5.0 by Citrus limon POD [54][55]. This study was in good agreement with [25], while in another report the best pH for decolorization of industrial effluent dyes by fenugreek peroxidase was also 5.0 [38].…”
Section: Application Of Sweet Lime Pod For Decolorizing Industrial Efsupporting
confidence: 92%
“…PODs extracted from different sources have been utilized for degradation of dyes, including horseradish peroxidase [24][25][26][27], soybean peroxidase [28], Cucurbita pepo [29], and white Spanish broom [30].…”
mentioning
confidence: 99%